Biphonal calls in Atlantic spotted dolphins (Stenella frontalis): bitonal and burst-pulse whistles. Issue 2 (3rd April 2018) - Kaplan, J. Daisy; Melillo-Sweeting, Kelly; Reiss, Diana
Abstract: Biphonation, the simultaneous production of two sounds by a single animal, is found in the vocalizations of a range of mammalian species. Its prevalence suggests it plays an important role in acoustic communication. Concurrent vocal and behavioural recordings were made of Atlantic spotted dolphins ( Stenella frontalis ) off Bimini, The Bahamas. The occurrence of two types of biphonal signals is reported: burst-pulse whistles with combined tonal and burst-pulse elements, and bitonal whistles. Biphonal whistles are rarely described in reports of dolphin acoustic repertoires, but were common in these dolphins: of all whistles analysed ( n  = 1211), 26.84% were burst-pulse whistles and 4.71% were bitonal whistles. A subset of whistles ( n  = 397) were attributed to dolphins of specific age classes, and used to compare prevalence of biphonation across age. Biphonation occurred in 61.54% of sexually mature and 48.32% of sexually immature dolphins' whistles. Sexually immature dolphins emitted more burst-pulse whistles than older dolphins: 44.13% of sexually immature dolphins' whistles were burst-pulse whistles, while 15.38% of adult whistles were burst-pulse whistles. Bitonal whistle production was more prevalent in sexually mature dolphins: 41.03% of adult whistles were bitonal, while only 4.19% of sexually immature dolphins' whistles were bitonal. The prevalence of a biphonal component in specific repeated, stereotyped whistle contours suggests that these acoustic features could be important components of contact calls, or signature whistles. The biphonal components of spotted dolphin whistles may serve to convey additional information as to identity, age or other factors to conspecifics.